Effect of H2O2 and Ascorbic Acid in β- Hemolysin Production from Clinical Isolates of Staphylococcus Aureus - Atyaf Ali Sahib (Journal of Global Pharma Technology, 2018)
Oxidizing agents and antioxidants are recently used in wound treatment and health care. The effect of such chemicals as H2O2 and ascorbic acid on beta hemolysin production by clinical isolates of Staphylococcus aureus (which were obtained from wound swabs) was investigated. Hemolytic activity was assayed semi- quantitatively (by measuring the diameter of the hemolytic zone around the wells in blood agar that contain the bacterial crude toxin) and quantitatively (hemolysis %) using the standard curve of osmotic hemolysis by Na Cl. The experiment  was optimized by selecting the optimum culture medium, type of blood, pH of the medium, incubation temperature, number of rpm in shaker incubator and incubation time. The higher production of the hemolysin was obtained when Staphylococcus aureus grown in the medium containing (0.05 mM) of H2O2 and (5  MM) of ascorbic acid, whereas the toxin production decreased in the media containing these substances in lesser concentrations.  Keywords: S. aureus, Hemolysin, H2O2, Ascorbic acid.Introduction